2019
DOI: 10.1002/dvdy.32
|View full text |Cite
|
Sign up to set email alerts
|

Stable transgenesis in Astyanax mexicanus using the Tol2 transposase system

Abstract: Background Astyanax mexicanus is a well‐established fish model system for evolutionary and developmental biology research. These fish exist as surface forms that inhabit rivers and 30 different populations of cavefish. Despite important progress in the deployment of new technologies, deep mechanistic insights into the genetic basis of evolution, development, and behavior have been limited by a lack of transgenic lines commonly used in genetic model systems. Results Here, we expand the toolkit of transgenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 49 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…Moreover, transgenic labeling of neurons in the brain permits tracing of neuronal projections, something that is not possible with Nissl staining (deCarvalho et al, 2013; Miyasaka et al, 2014). Whereas transgenic technology has not been widely used in A. mexicanus , recent studies have shown that the Tol2 system, which is widely used in zebrafish, is highly effective in A. mexicanus surface and cavefish (Elipot et al, 2014; Stahl et al, 2019a, b). Future work incorporating these tools would facilitate a highly defined neuroanatomical brain atlas for the A. mexicanus adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transgenic labeling of neurons in the brain permits tracing of neuronal projections, something that is not possible with Nissl staining (deCarvalho et al, 2013; Miyasaka et al, 2014). Whereas transgenic technology has not been widely used in A. mexicanus , recent studies have shown that the Tol2 system, which is widely used in zebrafish, is highly effective in A. mexicanus surface and cavefish (Elipot et al, 2014; Stahl et al, 2019a, b). Future work incorporating these tools would facilitate a highly defined neuroanatomical brain atlas for the A. mexicanus adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative efforts between multiple cavefish laboratories have yielded standardized procedures for Tol2 transgenesis, leading to the ability to produce stable transgenic lines that mark specific cell types Stahl, Peuß, et al, 2019). In addition to visualizing specific cell types, these methods can be extended into multiple areas of functional analysis, including performing comparative fate mapping, comparing brain activity to determine how sensory inputs affect brain activity in cave and surface fish, and activating or silencing different neuronal subtypes to dissect the neural circuits underlying behavioral evolution.…”
Section: Development Of Genetic Toolkits For Functional Interrogatimentioning
confidence: 99%
“…The transgenic zebrafish lines used in that study (Wee et al, 2019) do not exist in Astyanax CF. However, recent advances indicate that it may be now possible to perform this type of experiment in Astyanax fishes Stahl, Peuss et al, 2019).…”
Section: Subterranean Life With Scarce Foodmentioning
confidence: 99%